A Study of Distributed Database Management System - Shikha Mahajan; Dr. Leena Jain; Rupali (International Journal of Engineering and Management Research, 2023)
A Database is a collection of data describing the activities of one or more related organizations with a specific well defined structure and purpose. A Database is controlled by Database Management System (DBMS) by maintaining and utilizing large collections of data. Distributed computer applications built from off the shelf hardware and software are increasingly common at networked computers communicate and coordinate their activity only by-passing messages.[2] Distributed Database System the database is stored/spread physically across computers or sites in different locations that are connected by some form of data communication network. They may be spread over WAN or LAN. The computers may be of different types such as IBM Mainframes, VAXs, SUN workstation, PCs etc managed by different operating systems and each fragment of the data base may be managed by a different DBMS such as Oracle, Ingress, and Microsoft SOL server. This paper presents an overview of Distributed Database System[1]